Aktualisasi Nilai-Nilai Etik dalam Membentuk Efektifitas Budaya Organisasi Lembaga Pendidikan - Yusuf, M.; Masrokan Mutohar, Prim; Fuadi, Imam (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2024)
Organizational culture in educational institutions plays a vital role in creating an environment that supports the learning processes of students and their character development. This research aims to explore how the actualization of ethical values, such as honesty, responsibility, and mutual respect, can shape the effectiveness of organizational culture. The method used is library research, which involves in-depth analysis of various literature sources related to organizational ethics and educational management practices. The research findings indicate that the consistent application of ethical values in daily activities within educational institutions not only strengthens cooperation among staff but also enhances trust and commitment among all members of the organization. Additionally, this study finds that leaders who prioritize ethical values can create a conducive atmosphere for innovation and collaboration. Therefore, this research provides valuable insights for educational managers to further integrate ethical values into every operational aspect, aiming to create a more effective and harmonious organizational culture, which in turn can improve the quality of education provided